Proposal of a tourist guide of natural and cultural attractions in physical and digital format of the year 2018 for the parish GAD of Yaruquí canton Quito of the Pichincha province - Vicente Gutiérrez, Luis Patricio (Tierra Infinita, 2019)
In rural areas of the country, Ecuador has had shortcomings in tourism management as outdated tourist information and lack of official tourist information material. This fact caused an agreement between CONAGOPARE (National Council of Rural Parish Goverments) of Pichincha province and Yavirac Institute of Technology in Tourism and Heritage, this covenant was signed for the titlings projects, in wich this reality was investigated and solutions were proposed. Accordingly, the research in Rural Parish of Yaruqui was developed with a qualitative research method based on the idea, that tourist information was outdated and there was not available tourist information material, then the existing theoretical framework was reviewed and the researchers made an initial immersion in the field through meetings with authorities and field visits. After this validation, it was determinated by the researchers that this territory could effectively be the unit of analysis and beneficiary of a “Proposal of a Tourist Guide of natural and cultural attractives in physical and digital format of 2018 year to Parochial Government of Yaruqui Canton Quito in Province of Pichincha”, a process in which tourist survey and ICTs were applied in order to systematize in an adequate way the tourism reality of this rural territory.